KOLABORASI PEMERINTAH DALAM MERAIH PIALA PENGHARGAAN ADIPURA DI KABUPATEN LINGGA TAHUN 2018 - Amirudin "; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Adipura Program is contained in the Regulation of the Minister of Environment of the Republic of Indonesia No. 6 of 2014 concerning Guidelines for the Implementation of the Adipura Program in Chapter 1 General Provisions Article 1 that the Adipura Program is a national work of the Ministry of Environment to create an environmentally sound city towards sustainable development.This study aims to determine the Collaboration of the Lingga Regency Government in winning the 2018 Adipura Award Cup, and also to find out the supporting factors for the Lingga Regency Government in winning the 2018 Adipura Award Cup. Meanwhile, the location of this research was conducted in Lingga Regency, precisely at the Environmental Service Lingga Regency. This research uses qualitative research methods.The results of this study are collaboration in protecting the environment or Adipura activities between the Environmental Service and the community and the private sector have been optimally implemented, this is indicated by the presence of face-to-face dialogue, trust between stakeholders who are related to one another. And in terms of commitment of the parties involved, each of them has gone well. As for the supporting factors consist of two, namely internal factors and external factors. Internal factors, namely the support from agencies in Lingga Regency, and support from parties such as the Police, TNI, Satpol PP, and Damkar. Meanwhile, the external factor is the existence of good collaboration with the public and the private sector.Keywords: Collaboration, Awards, Adipura.